The Association Between Past Speech Therapy and Preseason Symptom Reporting in Adolescent Student Athletes. (26th July 2019) - Reese, K; Terry, D P; Maxwell, B; Zafonte, R; Berkner, P D; Iverson, G L
Abstract: Purpose: Neurodevelopmental conditions, such as ADHD, have been shown to be associated with different baseline symptom reporting, but the relationship between a history of speech therapy and symptom reporting is not well understood. This study examined the association between prior speech therapy and baseline symptom reporting in student athletes. Methods: A preseason baseline database contained 40, 378 athletes ages 13–18 who had not sustained a concussion in the past 6 months. Of these, 27, 550 athletes denied having all developmental/health conditions (controls) and 1, 497 reported only having history of speech therapy (total sample: age M=15.5, SD=1.26; 47% girls). Mann-Whitney U-Tests were used to compare baseline symptom reporting on the ImPACT® Post-Concussion Symptom Scale between athletes with prior speech therapy and controls. Individual symptoms were dichotomized (absent vs. present) and compared between groups using chi-square tests. Results: There was a higher proportion of boys in the prior speech therapy group than in the control group (62% vs. 53%; X 2 =41.9, p<.001). Athletes with speech therapy histories reported greater overall baseline symptoms (ps<.001). The effect sizes were minimal-to-small (Cohen's d: girls= 0.10; boys=0.20). Slightly higher portions of boys and girls with a history of speech therapy reported trouble falling asleep, fatigue, and difficulty concentrating/ remembering compared to their control counterparts (ps<.05). Further, compared to controls, a higher portion of boys (but not girls) with speech therapy histories reported physical and emotional symptoms. Conclusion: Adolescents with speech therapy histories report slightly more symptoms than controls during baseline testing, with a stronger effect in boys. However, effect sizes were very small.